2021
DOI: 10.1111/nph.17316
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative phase change in Populus tremula × alba

Abstract: Plants transition through juvenile and adult phases of vegetative development in a process known as vegetative phase change (VPC). In poplars (genus Populus) the differences between these stages are subtle, making it difficult to determine when this transition occurs. Previous studies of VPC in poplars have relied on plants propagated in vitro, leaving the natural progression of this process unknown.We examined developmental morphology of seed-grown and in vitro derived Populus tremula 9 alba (clone 717-1B4), … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 62 publications
2
23
0
1
Order By: Relevance
“…Populus tremula × alba line 717‐1B4 and two independent miR156 overexpressor lines, 40 and 78, described in Lawrence et al . (2020), were obtained by in vitro propagation and hardened on propagation media as described in Meilan & Ma (2006). Plants were then transplanted to Fafard‐2 growing mix (Sun Gro Horticulture, Agawam, MA, USA) in 0.3 l pots in a glasshouse at the University of Pennsylvania (39.9493°N, 75.1995°W, 22.38 m above sea level (asl)) and kept in plastic bags for increased humidity for 2 wk.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Populus tremula × alba line 717‐1B4 and two independent miR156 overexpressor lines, 40 and 78, described in Lawrence et al . (2020), were obtained by in vitro propagation and hardened on propagation media as described in Meilan & Ma (2006). Plants were then transplanted to Fafard‐2 growing mix (Sun Gro Horticulture, Agawam, MA, USA) in 0.3 l pots in a glasshouse at the University of Pennsylvania (39.9493°N, 75.1995°W, 22.38 m above sea level (asl)) and kept in plastic bags for increased humidity for 2 wk.…”
Section: Methodsmentioning
confidence: 99%
“…Leaves 1–52 were measured in poplar plants germinated from seed. The juvenile‐to‐adult transition in these plants occurred between leaves 20 and 30, as determined by the change in petiole shape and trichome density (Lawrence et al ., 2020). In Z. mays , leaves 2–11 were measured with leaves 1–5 juvenile in wild‐type plants and all leaves juvenile in Cg1 mutants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…or pear 21 by cycling expression year-round. Florigen action in the meristem to induce flowering 27 , 32 functions to transform the leaf into a mature organ changing its shape 33 and reducing its capacity to regenerate. While the phase change from vegetative to reproductive growth in a plant is accompanied by changing leaf shape 33 , we found that inducing early flowering and reducing regeneration ability is not related to this shape change.…”
Section: Discussionmentioning
confidence: 99%
“…Florigen action in the meristem to induce flowering 27 , 32 functions to transform the leaf into a mature organ changing its shape 33 and reducing its capacity to regenerate. While the phase change from vegetative to reproductive growth in a plant is accompanied by changing leaf shape 33 , we found that inducing early flowering and reducing regeneration ability is not related to this shape change. While the shape changes are correlated with reduced mir156 and increased SPL genes 33 , this study shows that independently from flowering and other meristematic effects, FT genes function in the leaf tissue as a determinant of juvenility or maturity depending if the rejuvenator or the florigen is expressed without changing the leaf shape that is typical of plant maturity.…”
Section: Discussionmentioning
confidence: 99%